Pengungkapan Tanggung Jawab Sosial dan Tata Kelola Perusahaan: Pengaruhnya Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Rasaningrum, Ruly; , Drs. Muhammad Abdul Aris, M.Si (2016)
This research is aimed to empirically examine the influence of corporate social responsibility and corporate governance on firm value. The corporate governance was identified by the commissaries board, independent commissaries board, audit committee, institutional ownership, manajerial ownership and audit quality. The corporate social responsibility was identified by Global Reporting Initiative index. This research was conducted with a purposive sampling method. This research used the secondary data from annual reports of manufacturing companies listed in Indonesia stock exchange during 2012-2014. The sample consisted of 48 annual report to analyzed (16 companies a year). The data are then analyzed by multiple regression with SPSS. The results show that corporate social responsibility, independent commissaries board, institutional ownership and manajerial ownership have a positive and significant influence on firm value; while the commissaries board and audit committee have a negative influence on firm value. Meanwhile the audit quality has no significant effect on firm value.